Computer-aided training and testing - Русаловський, А.В.; Кот, Т.М.; Кошуков, О.В. (Proceedings of National Aviation University (archive), 2007)
A range of tasks related to increasing efficiency of learning process and testing by means of information technologies and automation of those processes come under review in this article. Efficiency of learning and testing using traditional methods vs. analogous methods utilizing personal computers is compared. It is stated that utilizing computer enables to eliminate certain shortcomings of traditional learning and testing methods. Basic technological steps of learning and testing associated with using “Auto-Examinator” computer-based learning, testing software package are reviewed. Conclusions on benefits of use of computer-based learning and testing software for both teachers and students are drawn.